Polymorphism in two short tandem repeat loci (R-R and S-Q) linked to tRNA genes in Entamoeba dispar isolates - Mojarad, Ehsan Nazemalhosseini (Research Institute for Gastroenterology and Liver Diseases, 2012)
AIM: In this study, genetic polymorphism of two tRNA-liked short tandem repeat (STR)-containing loci, R-R and S-Q, was analyzed in order to clarify further the genotypic differences among E. dispar isolates. BACKGROUND: Entamoeba dispar is closely related to the human pathogen E. histolytica, the agent of amebic dysentery and amebic liver abscesses. E. dispar is, to some extent, capable of producing variable focal intestinal lesions in animals and of destroying epithelial cell monolayers in vitro, and some have reported it to be capable of producing amoebic liver abscess in hamsters. However no evidence exists at present to link E. dispar with human disease. PATIENTS AND METHODS: A total of 28 E. dispar samples from gastrointestinal disorder patients were characterized using PCR and sequencing. The sequences obtained were edited manually and aligned. RESULTS: Sequence analysis showed 9 and 6 different patterns of units in the repeat-containing region of R-R and S-Q, respectively. The repeat-containing regions of R-R and S-Q loci were found to be extensively polymorphic, varying in size, number and order of repeat units. CONCLUSION: The results demonstrate extensive genetic variability among Iranian E. dispar clinical isolates. The genetic diversity of tRNA gene-linked STR loci shows them to be suitable for epidemiological studies such as the characterization of the routes of transmission of these parasites in Iran.